Design of Microcontroller Based Fire Detector with Output Warning SMS Information and Automatic Extinguisher - Zain, Abdul; Hartono, Rudi; W, Sri Handani (INTEK: Jurnal Penelitian, 2020)
Conflagration is an unpredictable tragedy. It may occur whether in the woodland areas or in the residential areas. Typically, it would only be recognized if indeed the flames spread and the smoke intensified. This study aims to detect fires using the MQ-2 smoke sensor, DS18b20 temperature sensor, and fire sensor. Using Arduino Uno as the controller, this system’s output is in the form of an alarm buzzer, Short Message Service (SMS) information using SIM800L, and an automatic fire pump. This system operates to detect the temperature shifts, the smoke concentration and the existence of a fire point which triggers an alarm in the form of a siren if two out of the three sensors are activated. It, then, sends information by Short Message Service (SMS) and automatically triggers the pump as the result. The fire sensor can detect hotspots with a maximum distance of 80 cm and the DS18b20 temperature sensor has an average reading error of 0.27 ° C with a maximum reading error of 0.5 ° C. The MQ-2 smoke sensor can detect smoke where the change in smoke concentration is directly proportional to the sensor output voltage. There are three conditions to determine fire conditions, namely the temperature sensor reads more than equal to 55 ° C and the fire sensor is active, or the temperature sensor reads more than equal to 55 ° C and the smoke sensor reads more than equal to 1000 ppm, or the fire sensor is active and smoke sensor reads greater than equal to 1000 ppm.